Effect of fluoride-free and fluoridated carbamide peroxide gels on the hardness and surface roughness of aesthetic restorative materials - Homayoon Alaghehmand; Behnaz Esmaeili; Sina Arab Sheibani (Wolters Kluwer Medknow Publications, 2013)
Background: Bleaching products may show some side effects on soft and hard tissues and restorative materials in the oral cavity. This study evaluated the effect of carbamide peroxide gel with and without fluoride ions on the microhardness and surface roughness of tooth-colored restorative materials. Materials and Methods: In this in-vitro study, 76 cubic specimens (4 mm 3 × 4 mm 3 × 3 mm 3 ) were fabricated from 4 aesthetic A3-shade restorative materials. These materials consisted of two composite resins and two glass ionomers. The specimens made from each material were treated with the following surface treatments: 1. Control group: The specimens were not bleached and were stored in normal saline. Group 2. Fluoridated 20% carbamide peroxide gel, treated 3 h a day for 4 weeks. Group 3. Treated 1 h a day with fluoride-less 22% carbamide peroxide for two weeks. From each group, three other specimens were selected to be evaluated in terms of changes in surface roughness, under scanning electron microscopy (SEM). Results: In this study, fluoridated 20% carbamide peroxide gel increased the microhardness of the four aesthetic restorative materials. The fluoride-free carbamide peroxide 22% reduced the microhardness of the four used materials, which this change was significant for Vitremer and Amelogen. SEM analyses showed changes in surface roughness of glass ionomer specimens. Conclusion: The effect of bleaching on the microhardness of restorative materials is material dependent. Before the application of bleaching systems on the glass ionomer materials, the application of a protective barrier should be considered.